Effects of the health behavior modification program for weight control among students with overnutrition at Sida Subdistrict, Sida District, Nakhon Ratchasima Province - Chonpantarak, Choltira; Singsalasang, Atthawit (UBRU Journal for Public Health Research, 2025)
This quasi-experimental study aimed to examine the effects of a health behavior modification program for weight control among students with overnutrition in Sida Subdistrict, Sida District, Nakhon Ratchasima Province. The study employed a two-group, two-measurement design (equivalent pretest-posttest control group design). The sample consisted of 60 male and female students in grades 4–6 identified as having overnutrition. Participants were divided into an experimental group of 30 students from Wat Ban Hin Hae School and Wat Ban Don Koi School, and a control group of 30 students from Wat Ban Sida School. The intervention was conducted over a 12-week period. Data were analyzed using frequency, percentage, mean, standard deviation, paired-sample t-test, and independent-sample t-test. The results showed that after the intervention, the experimental group demonstrated significantly higher mean scores for self-efficacy (Mean diff = 3.10, 95% CI: 1.71–4.48, p < 0.001) and outcome expectancy (Mean diff = 3.16, 95% CI: 1.47–4.86, p = 0.001), as well as a greater reduction in mean weight (Mean diff = 0.55, 95% CI: 0.03–1.08, p = 0.039), compared to before the intervention. In the posttest comparison between the experimental and control groups, the experimental group had significantly higher self-efficacy (Mean diff = 2.97, 95% CI: 2.04–3.88, p < 0.001) and outcome expectancy (Mean diff = 2.93, 95% CI: 1.46–4.40, p < 0.001). However, no statistically significant difference was found in mean weight between the two groups (Mean diff = 1.58, 95% CI: –0.43 to 3.59, p = 0.121). Therefore, the implementation of health behavior modification programs should be considered as a strategy to control overnutrition among school-aged children.